COMMUNITY-BASED LOCAL WISDOM POTENTIAL OF NATURAL RESOURCES IN HUKURILA COUNTRY, AMBON ISLAND - Stellamaris Metekohy; Izaac T. Matitaputty; Maryam Sangadji; Terezia V. Pattimahu (SEAN Institute, 2023)
This research aims to describe the management and utilization of natural resources (SDA) based on local wisdom in Hukurila Country, Ambon Island. Where, local wisdom is a concrete manifestation of current natural resource utilization and management patterns without sacrificing the interests of future generations. The method used is a qualitative method with an ethnographic approach and scoring analysis. The research was conducted from May 2023 to September 2023, located in Hukurila State, Ambon Island. The results of the research show that the potential for natural resources in Hukurila Country in the form of agriculture (plantations) is one of the largest natural resource potentials, followed by the potential for beach tourism with diverse beach characteristics (white sand and white pebbles) and unique in Ambon City, namely, Tihulessy Beach and Zeu Beach. Management of natural resources based on local wisdom shows that the interpretation of the people of Hukurila Country regarding efforts to manage the country's traditions by being responsible for the development of sustainable development, such as the local wisdom of